2012
DOI: 10.1038/ajh.2012.91
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Is Not Independently Associated With Increased Aortic Stiffness in a Brazilian Population

Abstract: In conclusion, our study failed to provide evidence of a positive, blood pressure (BP)-independent association between obesity on aortic stiffness. Our data suggests that the previously reported finding of an association between obesity and aortic stiffness was probably confounded by the progressive increase in BP observed in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…It is important to note that any obesity marker (eg, BMI, weight, or WC) was associated with PWV. These findings are consistent with a previous study by our group22 in which both BMI and WC increased BP levels. When adjusted for BP level, the association between obesity indices (confounders) and cf‐PWV disappeared.…”
Section: Discussionsupporting
confidence: 94%
“…It is important to note that any obesity marker (eg, BMI, weight, or WC) was associated with PWV. These findings are consistent with a previous study by our group22 in which both BMI and WC increased BP levels. When adjusted for BP level, the association between obesity indices (confounders) and cf‐PWV disappeared.…”
Section: Discussionsupporting
confidence: 94%
“…In another study, an increase in waist circumference has also been found to be independently associated with higher cfPWV values among youth with type 1 diabetes (Dabelea et al 2013). However, in contrast, yet another study has noted that cfPWV values are correlated positively with BMI, but are not correlated with waist circumference in a Brazilian population (Rodrigues et al 2012). Increased aortic stiffness, a major mechanical factor predicting cardiovascular risk, has been clearly identified as playing a role in MetS (Safar et al 2013).…”
Section: Discussionmentioning
confidence: 80%
“…However, inverse association, 58 or absence of association after adjustment for blood pressure 59 between PWV and visceral obesity were also reported in other studies, indicating the need for additional investigations to detect the causal link between these phenotypes.…”
Section: Review Articlementioning
confidence: 88%